COMPARATIVE ANALYSIS OF THE FREQUENCY OF CYTOGENETIC ABNORMALIES IN THE ROOT APICAL MERISTEM OF SPRING BARLEY (HORDEUM VULGARE L.) CULTIVAE SEEDLINGS, CONTRASTING IN THEIR LEAD TOLERANCE - A. V. Dikarev; V. G. Dikarev; N. S. Dikareva (Труды по прикладной ботанике, генетике и селекции)
Cell division activity, frequencies and spectra of cytogenetical abnormalities were studied in the root apical meristem cells of spring barley seedlings (Hordeum vulgare L.). Comparative analysis of aberration frequencies in cells of most sensitive or tolerant barley cultivars was made. Sensitive and tolerant cultivars of spring barley were chosen by testing of lead influence on 100 barley cultivars from the VIR collection. Significant differences between groups of sensitive and tolerant cultivars were shown in indexes received on intact seedlings: frequencies of aberrant cells (FAC), frequency of cytogenetical abnormalities on a dividing cell (FADC), frequency of cytogenetical disturbances on a cell with cytogenetical abnormalities (FAAC). Mechanisms of tolerance to lead and HM were discussed.